Palladium-Catalyzed C–H Bond Arylation and O- to N-Alkyl Migratory Rearrangement of 2-Alkoxythiazoles: One-Pot Access to 2-Alkoxy-5-arylthiazoles or 3-Alkyl-5-arylthiazol-2(3H)-ones - Huang, Hai-Yun; Li, Haoran; Cordier, Marie; Doucet, Henri (Synthesis, 2022)
Pd-catalyzed direct arylation of 2-alkylthiazoles is a well-known reaction affording the corresponding 2-alkyl-5-arylthiazoles in very high yields. Conversely, the reactivity of 2-alkoxythiazoles has not been described yet. Herein, we report conditions for the Pd-catalyzed regioselective C5-arylation of 2-alkoxythiazoles. Moreover, we also found reaction conditions leading to 3-alkyl-5-arylthiazol-2(3H)-ones via a one-pot direct arylation with an O- to N-alkyl migratory rearrangement. The judicious choice of reaction temperature and time allows control over the selectivity of the reaction. In general, at 100 °C, 2-alkoxy-5-arylthiazoles were the major products, whereas, at 120 °C with a longer reaction time, 3-alkyl-5-arylthiazol-2(3H)-ones were obtained with good selectivities. The arylation reaction is promoted by a ligand-free air-stable palladium catalyst and a simple and inexpensive base, without oxidant or further additives, and tolerates a variety of useful substituents on the aryl bromide and also heteroaryl bromides.
Keywords: palladium catalysis; C–H functionalization; arylation; migratory rearrangement; thiazoles; thiazolones